Children with Asthma Exposed to COVID-19 Show a Decrease in Severity from Baseline: A Systematic Review from March 2020 to September 2022 - Chowdhury, Juel; Ravi, Rejoice Puthuchira; Mundodan, Jesha Mohammed Ali; Mohamedbek, Hayat; Albayat, Soha Shawqi (British Journal of Healthcare and Medical Research, 2022)
Introduction: During the COVID-19 pandemic, children have been affected by SARS- CoV-2 infection, primarily affecting the respiratory system. Children with chronic respiratory diseases such as asthma, emphysema, and chronic bronchitis can experience an exacerbation of the preexisting conditions. The study's primary aim was to identify the severity of asthma in COVID-19-exposed children aged 4-12 years. Methods: We extracted the data from the PubMed database between March 2020 and September 2022. During the COVID-19 pandemic, PubMed-published articles involving children living with asthma aged 4-12 years were identified. The study included children who had tested positive for SARS-CoV-2 and excluded children with any other comorbidities. Results:We identified 169 PubMed- published articles and filtered 28 articles. Seven articles met the inclusion criteria and were included in the study. The children with asthma hospitalized owing to COVID-19 worldwide was 1% to 2.7%. Incidence was 12.8 times less frequent in children than in adults. Increased expression of the angiotensin-converting enzyme-2 gene in the bronchial epithelium of patients with type 2-low or T1-high asthma tended to have higher known risk factors for COVID-19. Among school-age children (N=277,285), 1.2% were hospitalized, 0.1% had intensive care unit admissions, and <0.1% died. Of those patients (hospitalized, ICU admissions, and those who died from COVID-19), all had at least one underlying medical condition, and 55% had chronic lung disease, including asthma. Conclusion: Most children with recurrent wheezing and asthma were well-controlled by their underlying asthma and did not require significant changes to their maintenance treatments. It concludes that children who tested positive for SARS-CoV-2 had fewer pediatric hospital admissions and attendance at urgent care settings. The reduction in asthma morbidities is due to improved adherence and decreased exposure to allergens and viral infections in children.